Nanoscopic Single-Incision Anterior Labrum Repair - Lavender, Chad (Arthrosc Tech, 2020)
Arthroscopy frequently has been used to treat a variety of shoulder conditions, including anterior labrum tears. Anterior labrum repair techniques have progressed from multiple incision techniques to most recently a single anterior working portal with a posterior viewing portal. With the development of the NanoScope (Arthrex, Naples, FL), we do not need to make a standard portal for viewing purposes. In this article, we describe the single-incision anterior labrum repair bypassing the need for a posterior skin incision. The removal of this incision and portal should result in less fluid needed and less swelling. We hope this leads to less pain and improved patient outcomes.